1998
DOI: 10.1002/(sici)1097-0142(19980215)82:4<697::aid-cncr12>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione concentration may be a useful predictor of response to second-line chemotherapy in patients with ovarian cancer

Abstract: Second-line chemotherapy consisting of etoposide and cisplatin is effective in the treatment of relapsed epithelial ovarian cancer. In addition, tumor concentration of GSH may be a useful predictor of the response to this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 15 publications
(2 reference statements)
0
39
0
Order By: Relevance
“…5,6 However, this invaluable function is disadvantageous during chemotherapy, when enhanced detoxification by the glutathione/GST pathway may result in tumor resistance to cytotoxic agents. 20 Previous in vitro investigations and clinical studies have demonstrated that high levels of GST enzymes in tumors are associated with weaker responses to chemotherapy and poorer survival in patients with carcinomas of the breast, 21 stomach, 22 esophagus, 23 ovary, 24,25 and head and neck. 26 To our knowledge, only two studies on GSTP1 polymorphisms and breast carcinoma survival, conducted in the United States 14 and the United Kingdom, 15 respectively, have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, this invaluable function is disadvantageous during chemotherapy, when enhanced detoxification by the glutathione/GST pathway may result in tumor resistance to cytotoxic agents. 20 Previous in vitro investigations and clinical studies have demonstrated that high levels of GST enzymes in tumors are associated with weaker responses to chemotherapy and poorer survival in patients with carcinomas of the breast, 21 stomach, 22 esophagus, 23 ovary, 24,25 and head and neck. 26 To our knowledge, only two studies on GSTP1 polymorphisms and breast carcinoma survival, conducted in the United States 14 and the United Kingdom, 15 respectively, have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…4e), hydrazones 57,138 and esters that are hydrolysed at the acidic pH found in many endosomes 137 , has become a popular strategy for intracellular drug release. Other chemistries that lend themselves to intracellular drug release include disulphide reduction 139 (FIG. 4a,b) and endosomal enzyme hydrolysis [140][141][142] (FIG.…”
Section: Self-cleaving Linkersmentioning
confidence: 99%
“…Oxidative stress causes profound alterations of various biological structures including cellular membranes, lipids, proteins and nucleic acids. Oxidative stress is considered to be involved in aging [44][45][46][47][48][49][50][51] and in various diseases such as diabetes mellitus [52][53][54], atherosclerosis [55,56], rheumatoid arthritis [57][58][59][60], Alzheimer's disease [61][62][63], Parkinson's disease [64][65][66] and cancer [67][68][69][70][71]. There is an increasingly growing interest in identifying biomarkers for diseases in which oxidative stress is involved [72].…”
Section: Oxidative Stressmentioning
confidence: 99%